2014
DOI: 10.4028/www.scientific.net/amr.1040.53
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surfactants on the Structure and Wear Resistance of Copper Alloyed Hypereutectoid Steel

Abstract: Influence of modifying with silicocalcium (SiCa) on the structure and friction properties of the hypereutectoid steel alloyed with 8.85 wt. % of Cu was studied. SiCa modifying of the copper alloyed hypereutectoid steel, led to the formation of the vermicular graphite distributed in the indendritic space instead of cementite. Coefficient of friction reduction and increased wear resistance were marked in the copper alloyed hypereutectoid steel due to the presence of graphite and cupric inclusions in the steel st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…The analysis of the microstructure of tin-base bronzes in different sample sections has shown that the reduction of mechanical characteristics occurs due to increased shrinkage porosity and coarsening of lead impurities in thick sections [5]. At low h values there is significant refinement of dendritic lattice of α-solution, which conditions the increase of mechanical properties [6].…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the microstructure of tin-base bronzes in different sample sections has shown that the reduction of mechanical characteristics occurs due to increased shrinkage porosity and coarsening of lead impurities in thick sections [5]. At low h values there is significant refinement of dendritic lattice of α-solution, which conditions the increase of mechanical properties [6].…”
Section: Resultsmentioning
confidence: 99%
“…This paper presents the results of studying the effect of copper oxide nano-particles in the iron-based charge on the intensity of wear and score resistance of coatings obtained with laser cladding. I ron-based alloys doped with copper can be attributed to anti-friction materials [1][2][3][4][5]. A decrease in the coefficient of friction for lowcarbon steel [1] and cast iron [2] was noted when copper is added.…”
Section: Obtaining Wear-resistant and Score-resistant Coatings With Imentioning
confidence: 99%
“…The decrease in the friction coefficient depend on the concentration of coppercontaining particles ranging in size from several nanometers to tens of micrometers. Such particles can be formed, both during prolonged isothermal annealing of hardened steel [6][7][8][9] and during crystallization of cast iron-carbon alloys [1][2][3][4].…”
Section: Obtaining Wear-resistant and Score-resistant Coatings With Imentioning
confidence: 99%
See 2 more Smart Citations